Rancang Bangun Smart Robot Omni Wheel sebagai Permainan Edukatif dan Interaktif bagi Balita - Muhammad Nur; Tantri Indrabulan (PROtek : Jurnal Ilmiah Teknik Elektro, 2021)
The purpose of this research is to produce a smart robot prototype that is able to attract toddlers' attention so that they can respond in the form of motor movements. The making of smart robots will be adjusted to the needs of toddler stimulation in the form of movement interactions approaching or away from objects so that toddlers are triggered to chase or avoid the robot. Educational games that are designed appropriately for toddlers can improve their motor development. This can occur due to stimulating activities from educational games that can stimulate the toddler's brain. Smart robots are one of the educational game technology products that apply the concept of the industrial revolution 4.0. The smart robot prototype design will use the Arduino Mega microcontroller. The microcontroller input is obtained from a proximity sensor that is implanted in the robot's body. The essence of the smart robot in this study is a dynamic and very flexible robot movement caused by the use of the omni wheel as a driving wheel.